Confirmation of the recognition of Culiseta (Culiseta) indica Edwards, 1920 as a distinct species based on integrated morphological and molecular data - Natarajan, R.; Gopalakrishnan, S.; Talib, H.d.; Kumar, N. Pradeep; Shriram, A.n.; Kumar, Ashwani; Jambulingam, P. (Zootaxa, 2024)
Theobaldia indica Edwards, 1920, classified as a subspecies of Culiseta (Culiseta) alaskaensis (Ludlow, 1906), was recently restored to its original species status, as Culiseta (Culiseta) indica (Edwards), based on comprehensive assessments of morphological, ecological and distributional data. Predating the recognition of indica as a separate species, we collected specimens of this nominal taxon in the Western Himalayan region of India during 2015–2017, and used morphological and molecular studies to assess its taxonomic status. Our detailed examination of adult morphology, male genitalia and larval characteristics revealed significant distinctions between putative Cs. alaskaensis alaskaensis and Cs. alaskaensis indica, and sequencing of the barcode region of the mitochondrial COI gene yielded a Kimura 2 parameter genetic distance of 5.9% between them, well above the standard 2‒3% commonly accepted to indicate separate species. These results strongly support the formal recognition of Cs. indica as a separate species. Furthermore, the geographical distribution of Cs. indica provides additional evidence in support of its species status.